The Manichaeans of the Roman East : Manichaeism in Greek anti-Manichaica & Roman Imperial Legislation - Matsangou, Rea (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2024., 2023)
The Manichaeans of the Roman East is the first monograph that synthesizes an enormous body of primary material to reconstruct the history of East-Roman Manichaeans, from the time their first missionaries arrived in the territory of the Roman East until the disappearance of Manichaeism from the Eastern Roman Empire. Through her systematically comparative and intertextual investigation of the sources, Matsangou provides a number of original approaches to issues such as the classification of Manichaeism, the socio-religious profile and lifestyle of East Roman Manichaeans, the triggers of the severe anti-Manichaean persecutions. She thoroughly analyses the relationship between Manichaean and Christian ascetics for the first time, suggesting a possible Manichaean impact on the rise of ascetic manifestations among Christian ascetics, monks, and individuals in society. By considering the dimensions of the phenomenon of crypto-Manichaeism and using the concept of "entryism"-borrowed from politics-as a theoretical model, Matsangou makes intriguing hypotheses suggesting an alternative explanation for the disappearance of Manichaeism from the Roman East.